Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1128/aac.46.6.1634-1639.2002
|View full text |Cite
|
Sign up to set email alerts
|

Internal Thiols and Reactive Oxygen Species in Candidacidal Activity Exerted by an N-Terminal Peptide of Human Lactoferrin

Abstract: We previously showed that the energized mitochondrion and extracellular ATP are essential for the candidacidal activity of the N-terminal peptide of human lactoferrin, subsequently referred to as hLF(1-11). The present study focuses on the involvement of internal thiols and reactive oxygen species (ROS) in the candidacidal activity exerted by hLF(1-11). Our results reveal that hLF(1-11) reduced the internal thiol level of Candida albicans by 20%. In agreement, N-acetyl-L-cysteine (NAC), which is a precursor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 42 publications
(105 reference statements)
2
27
0
4
Order By: Relevance
“…Another study demonstrated the involvement of fungal endogenous thiols and reactive oxygen species (ROS) in the candidacidal activity exerted by hLf (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In this study, hLf(1-11) caused a decrease in the internal thiol levels of Candida albicans by 20% and an increase in the level of its production of ROS in a dose-dependent manner; a correlation between ROS production and candidacidal activity was also found [51].…”
Section: In Vitro Antibacterial and Anti-fungal Activity Of Lf(1-11)mentioning
confidence: 61%
“…Another study demonstrated the involvement of fungal endogenous thiols and reactive oxygen species (ROS) in the candidacidal activity exerted by hLf (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In this study, hLf(1-11) caused a decrease in the internal thiol levels of Candida albicans by 20% and an increase in the level of its production of ROS in a dose-dependent manner; a correlation between ROS production and candidacidal activity was also found [51].…”
Section: In Vitro Antibacterial and Anti-fungal Activity Of Lf(1-11)mentioning
confidence: 61%
“…Each lobe is capable of binding one Fe 3ϩ ion together with one CO 3 2Ϫ ion in a deep intralobe cleft that contains a nonheme iron-binding site (1). The noniron-dependent activities of human lactoferrin have been shown to be mediated by a 47-residue peptide (corresponding to residues 1 to 47 of the mature human lactoferrin protein) that is released upon cleavage of human lactoferrin with pepsin (5,6,8,27,28,35,46). These residues form a ␤-␣-␤ unit located on the exposed surface of the human lactoferrin protein that is distinct from the iron-binding region.…”
mentioning
confidence: 99%
“…3) Moreover, ROS generation is involved in the mechanisms of many antifungal agents. [4][5][6] Oxidative stress could therefore be a frequent challenge for C. albicans to survive and cause diseases in its host.…”
mentioning
confidence: 99%